Making our way home : the Great Migration and the Black American dream - Imani, Blair (Ten Speed Press, 2020)
"A powerful illustrated history of the Great Migration and its sweeping impact on Black and American culture, from Reconstruction to the rise of hip hop. Over the course of six decades, an unprecedented wave of Black Americans left the South and spread across the nation in search of a better life--a migration that sparked stunning demographic and cultural changes in twentieth-century America. Through gripping and accessible historical narrative paired with illustrations, author and activist Blair Imani examines the largely overlooked impact of The Great Migration and how it affected--and continues to affect--Black identity and America as a whole. Making Our Way Home explores issues like voting rights, domestic terrorism, discrimination, and segregation alongside the flourishing of arts and culture, activism, and civil rights. Imani shows how these influences shaped America's workforce and wealth distribution by featuring the stories of notable people and events, relevant data, and family histories. The experiences of prominent figures such as James Baldwin, Fannie Lou Hamer, El Hajj Malik El Shabazz (Malcolm X), Ella Baker, and others are woven into the larger historical and cultural narratives of the Great Migration to create a truly singular record of this powerful journey"--